2012
DOI: 10.4315/0362-028x.jfp-11-236
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Listeriosis Outbreak Attributable to Pasteurized Cheese, Which Led to Extensive Cross-Contamination Affecting Cheese Retailers, Quebec, Canada, 2008

Abstract: A major Listeria monocytogenes outbreak occurred in the province of Quebec, Canada, in 2008, involving a strain of L. monocytogenes (LM P93) characterized by pulsed-field gel electrophoresis (PFGE) and associated with the consumption of pasteurized milk cheese. This report describes the results of the ensuing investigation. All individuals affected with LM P93 across the province were interviewed with a standardized questionnaire. Microbiological and environmental investigations were conducted by the Quebec's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 22 publications
(29 reference statements)
2
43
0
4
Order By: Relevance
“…Scenario i is supported by a previous study that showed transfer of a persistent L. monocytogenes strain with dicing equipment transferred from one processing plant to another (56). Scenario ii is supported by a previously reported multistate U.S. outbreak of listeriosis linked to turkey deli meat (54) and a widespread outbreak of listeriosis in Quebec, Canada, linked to pasteurized cheese (57). In the former report, L. monocytogenes identical, as determined by PFGE, to the outbreak strain were isolated from three delis and subsequently the source of contamination was traced back to persistent L. monocytogenes contamination (over up to 12 years) at a deli meat processor that supplied each of these delis (54).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Scenario i is supported by a previous study that showed transfer of a persistent L. monocytogenes strain with dicing equipment transferred from one processing plant to another (56). Scenario ii is supported by a previously reported multistate U.S. outbreak of listeriosis linked to turkey deli meat (54) and a widespread outbreak of listeriosis in Quebec, Canada, linked to pasteurized cheese (57). In the former report, L. monocytogenes identical, as determined by PFGE, to the outbreak strain were isolated from three delis and subsequently the source of contamination was traced back to persistent L. monocytogenes contamination (over up to 12 years) at a deli meat processor that supplied each of these delis (54).…”
Section: Discussionsupporting
confidence: 62%
“…These cases suggest persistence of a strain representing a given clade at an external site, which serves as a source of introduction into multiple delis. A strain could persist at a supplier facility and be introduced to multiple delis through product shipments, as suggested in a 2008-2009 listeriosis outbreak from pasteurized Mexican-style cheese (58), and consistent with the studies cited above (54,57). Alternatively, a given strain with a recent MRCA could be a recently emerged, evolutionary successful strain found across multiple source environments.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Historically, lineage I 4b strains have been overrepresented in clinical listeriosis cases and are less frequently recovered from foods (8)(9)(10). However, over the past decade, lineage II 1/2a strains typically overrepresented in food and environmental samples (3,9,11) have been frequently linked to human disease, causing notable outbreaks in Switzerland (12) and the United Kingdom and two 2008 outbreaks in Canada (7,13). With regard to the Canadian outbreaks, 1/2a strains comprise the majority of Canadian clinical isolates, followed by 4b (14).…”
mentioning
confidence: 99%
“…This is the most commonly used molecular subtyping method for surveillance and outbreak detection because of its high discriminatory power and reproducibility (Deng et al, 2016). PFGE was used for the molecular subtyping of Listeria monocytogenes isolates in a commercial cheese made from pasteurized milk that caused an outbreak in Germany from October 2006 through February 2007 (Koch et al, 2010) and in Quebec, Canada, in 2008(Gaulin et al, 2012. Additionally, in 2010, this technique was useful in determining the genotypic diversity of Listeria monocytogenes in the acid curd cheese that caused a multinational outbreak between 2009 and 2010 (Schoder et al, 2014).…”
Section: Pulsed Field Gel Electrophoresismentioning
confidence: 99%